Oestrus cycle, female reproductive system morphology and temperament and sperm attribute of rusa deer (Rusa timorensis Blainville) in captivity - Mahre, Mohammed Bakari (2014)
The reproductive biology of the Rusa deer (Rusa timorensis) farmed in Malaysia is not known. Therefore, this study was conducted to determine certain aspects of the reproductive biology of R. timorensis raised in the tropics with the objectives to investigate the temperament, describe the morphology of the female reproductive system, establish the oestrous cycle, develop a reference data for evaluation of reproductive status of R. timorensis and determine the oestrus response and pregnancy rate following oestrus synchronization with cloprostenol and natural mating as well as to determine the fertility potentials of the male R. timorensis through semen collection and evaluation. Seventeen adult R. timorensis hinds were selected for evaluation of temperament. To evaluate the temperament, well established methods from previous studies on cattle and red deer were adopted using flight time, crush test score and plasma cortisol assay. Description of the morphology of the female reproductive system were performed on two adult hinds after slaughter. Different reproductive structures were measured using a pair of calipers and a long string. Histology and Scanning Electron Microscopy were done according to the standard methods. To establish the oestrous cycle, five healthy adult hinds were selected for peripheral blood sampling to gauge the plasma progesterone levels by radioimmunoassay. Vaginal smears were also taken to characterize the oestrus stages of R. timorensis using vaginal cytology. Semen were collected from two and five fertile stags during the first and second breeding season respectively for semen evaluation. Semen samples were collected from the stags using an electro-ejaculator. The ejaculate was processed and samples prepared for light and scanning electron microscopy (SEM) according to standard methods. To determine the oestrus response and pregnancy rate in R. timorensis following oestrus synchronization with a prostaglandin analogue, oestrus was synchronized in eight cycling hinds with 500 µg cloprostenol given intramuscularly at 10 days apart. Eight other R. timorensis hinds were notsynchronized and served as control. Blood samples, collected every three to four days for 29 days from the first cloprostenol injection, were analyzed for plasma progesterone concentrations. Oestrus was recorded based on observation of oestrus signs during the period of blood sampling. The hinds were bred 24h after the second cloprostenol injection and all hinds were subjected to transrectal ultrasonography to assess pregnancy status. The results of this study have demonstrated that flight time, crush score and plasma cortisol concentration could be used for selecting R. timorensis © COPYRIGHT UPM ii based on temperament for the breeding herd. The morphology of the female reproductive system of R. timorensis is similar to that observed in domestic ruminants except that the uterus did not have an interconual ligament and unlike domestic ruminants, the left ovary is slightly larger than the right ovary which indicates that it is physiologically more active. Unlike the cows and goats, the cervix of R. timorensis is characterized by six cervical rings projecting into the cervical canal. This feature should taken into account when designing an Artificial insemination catheter for transcervical passage of semen during Artificial insemination in this species. Two cell types were observed in the epithelium of the reproductive tract: ciliated cells and nonciliated secretory cells. Based on the cyclic basal plasma progesterone levels and the observations of changes in the cellular pattern of the vaginal epithelium, the mean length of oestrous cycle of R. timorensis deer farmed in Malaysia was estimated to be 19.2 ± 1.3 days with a range of 18 to 21 days. On the basis of changes in plasma progesterone concentrations, cloprostenol (prostaglandin analogue) induced oestrus in only five of the eight treated hinds. The other three treated hinds showed progesterone values (0.8 ng/mL) which appeared to be too low to indicate presence of a corpus luteum for the drug to act on. Five treated hinds and four control hinds displayed standing oestrus. Conception occurred in four treated and four control hinds. In the present study, oestrus synchronization has been successfully achieved using prostaglandin analogue. However, future studies need to refine synchronization regimes to increase oestrus synchrony and pregnancy rate. No significant difference (P˃0.05) was found between sperm attributes in comparison between different stags and different months of the fertile seasons. Semen volume as well as pH, sperm concentration, general motility, progressive motility, and viability were 2.2±0.29 ml, 7.2±0.17, 886.3±39.7×106 spermatozoa/ml, 78.7±2.01 %, 80.8±1.85 % and 83.2±0.85 % respectively. Morphological analysis showed low percentage (13.9±2.88 %) of abnormal spermatozoa. In conclusion, the study provided baseline data on the reproductive biology of male and female R. timorensis, which will facilitate future researches that would lead to propagation of this vulnerable species of animal. The results obtained from this study can be used as a general reference by deer farmers in Peninsular Malaysia and local zoos to evaluate the reproductive status of R. timorensis.